2018
DOI: 10.3390/su10061746
|View full text |Cite
|
Sign up to set email alerts
|

Study on Application Potential of Seasonal Thermal Energy Storage-Hybrid Ground Source Heat Pump in Taiwan—Taking Experiments in Tainan as Examples

Abstract: Ground source heat pumps (GSHPs) are widely used in building energy conservation in many countries and regions. However, they are rarely seen in Taiwan. The main reason is the extraordinary imbalance between the heating load and cooling load of buildings in Taiwan. Hybrid ground source heat pump (HGSHP) is a hybridization of a traditional GSHP system, and can effectively balance the heat injected into and extracted from the ground over an annual cycle. This study focuses on the application of seasonal thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The simulation results showed that the imbalance efficiencies and annual average soil temperature decreases were not the same in the different regions. Therefore, GSHPs are rarely adopted in areas that have extraordinarily imbalanced heating and cooling loads [16]. However, there are often obvious differences between the cooling and heating loads in actual operation due to the climates in different regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation results showed that the imbalance efficiencies and annual average soil temperature decreases were not the same in the different regions. Therefore, GSHPs are rarely adopted in areas that have extraordinarily imbalanced heating and cooling loads [16]. However, there are often obvious differences between the cooling and heating loads in actual operation due to the climates in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GSHPs are rarely adopted in areas that have extraordinarily imbalanced heating and cooling loads [16].…”
Section: Introductionmentioning
confidence: 99%